Sepsis after splenectomy: prophylaxis and treatment - Araújo-Filho, Irami; Souza, Sérvulo Marciano Pinheiro de; Ferreira, Juliana Beatriz de Oliveira; Rêgo, Amália Cínthia Meneses; Felipe, Jéssica Carvalho; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2014)
Infection is very important for the patient underwent splenectomy follow up, not only for the prevalence, but the lethality of disease. The following review is to summarize practical informations about the extent of knowledge of etiology, diagnosis, treatment and prophylaxis. The treatment starts early and appropriate prophylaxis are decisive for the prognosis of asplenia, being the focus of this study. To carry out this work a review of relevant literature of the last decade was taken. As a result, we emphasized extensively about the treatment and prophylaxis of the disease, but the large number of fatal outcomes, found until today, indicates that studies on early diagnosis and early treatment as well as prophylaxis, need to be improved.